Optical switching based 2D materials/antennas hybrid system - Li, Siming (Nanyang Technological University, 2022)
Singapore has proposed the smart nation project since 2017. Moreover, Singapore has stepped into industry 4.0, advanced manufacturing. This means our country and work lifestyle become more digitalized. However, the traditional CMOS transistor is going to reach the size limit. Hence a new type of transistor needs to be developed. Optical switches give us an alternative way. The strong coupling between plasmon and exciton is one of the ways to do the optical switch. In this final year project, we use the two-dimensional WS2 and noble metal gold to design three planar nano antennae to archive the strong coupling effect. The splitting can be successfully adjusted by modifying the geometry of the nanoantenna arrays, including shape, side length, and gap size. The three structures are single square structure, square dimer structure and the disk dimer structure. The maximum splitting of 298meV has been achieved in this project.